The Effect of Steel Fiber Content on The Splitting Tensile Strength of Steel Fiber Reinforced Concrete (SFRC) - Mentari S. Sitorus; Indah N. Afiah; Zulfadli Ibrahim; Andi Firman Muhibuddin (Institut Teknologi Sepuluh Nopember (ITS), 2025)
Concrete is a composite material consisting of two main components namelyaggregate and cement mortar as a binder. Concrete has high compressive strengthbut weak tensile strength. The addition of fiber in concrete can improve ductilebehavior before collapse, inhibit the growth of crack expansion and increasedurability. This study aims to examine the effect of fiber content on themechanical properties of fiber concrete. The fibers used were ssteel fibers withhooked end, and l/d ratio = 67,7 mm with normal concrete quality f’c = 25 MPa.The percentage of fiber content used in this study was 0%, 0,1%, 0,2%, 0,3%,0,5%, 0,75%, 1%, 1,5% and 2%. The results showed that the addition of fiber inconcrete was able to increase the split tensile strength by 7 – 117%. Fiber concretehas higher ductility than normal concrete. This is indicated by the high deflectionof fiber concrete compared to the deflection of normal concrete under load.